Rancang Bangun Aplikasi Manajemen Medical Record Pasien dengan Restful API: Optimalisasi Efisiensi dan Keamanan Data Klinik - Bayu Fadlan Rosid; Sartika Lina Mulani Sitio (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2026)
Manual medical record management in many clinics often leads to various problems such as long queues, slow service, data loss risks, and limited information exchange among medical personnel. This study aims to design and develop a web-based medical record management application integrated with a RESTful API to enhance operational efficiency and data security in clinical environments. The development process includes requirements analysis, database and UML design, system implementation, and evaluation using Black Box Testing and the System Usability Scale (SUS). The results indicate that the system successfully streamlines patient registration, queue management, medical examinations, prescription processing, and inpatient services in a more structured and efficient manner. Black Box Testing confirms that all core features operate properly, while the SUS evaluation involving 15 respondents produced an average score of 71.5, categorized as “Acceptable”. Therefore, the proposed system is considered feasible for use and capable of improving data accuracy, service speed, and integrated information flow within the clinic.